RCP8.5-projected changes in German Bight storm surge characteristics from regionalized ensemble simulations for the end of the twenty-first century - Mayer, Bernhard; Mathis, Moritz; Mikolajewicz, Uwe; Pohlmann, Thomas (Frontiers in Climate, 2022)
This study investigates climate-induced changes in height, frequency and duration of storm surges in the German Bight. The regionally coupled climate model system MPIOM-REMO with a focus on the North Sea has been utilized to dynamically downscale 30 members of the global climate model system MPI-ESM1.1-LR for the historical period 1950–2005 and a continuation until 2099 with the RCP8.5 scenario. Results of all members have been collected into the historical (1970–1999) and the rcp85 ( 2070–2099) data pools amounting to 900 years of the corresponding climate state. The global mean sea level rise was not considered. Nevertheless, the mean ensemble German Bight SSH trend amounts to about 13 ± 1 cm/century (PI control: 3 cm/century) due to adaptation of the ocean circulation to the changing climatic conditions. Storm surges were defined as SSH above mean high tidal water plus 1.5 m, 2.5 m, 3.5 m for “regular”, heavy, extreme storm surges, and then clustered to events. Our simulated storm surge events show a clear location-dependent increase in frequency (6-11 %), median duration (4-24 %) and average duration (9-20 %) in the German Bight. Only along the central German Bight coast (Cuxhaven), longer lasting events gain more relevance. Heavy storm surge events show also a strong increase in frequency (7-34 %) and average duration (10-22 %). Maximum sea levels during storm events increase strongest and most significant along the northern German Bight and Danish coasts with more than 30 cm/century for the 60-year return period at Hörnum and 10-15 cm/century for shorter return periods. Levels of return periods shorter than a few years significantly increase everywhere along the southern German Bight coasts (around 5 cm/century for the 2-year return period). Highest SSH maxima do not change, and consequently, extreme storm surge events show hardly any response to climate change. Furthermore, our results indicate a shift of seasonality from the last to the first quarter of a year. As the main driver for the encountered alteration of German Bight storm surge characteristics, we identified a change in wind conditions with a pronounced increase of frequency of strong westerly winds.